Effectiveness of Prenatal Intervention on the Outcome of Diseases That Have a Postnatal Urological Impact - Bañuelos Marco, Beatiz; González, Ricardo; Ludwikowski, Barbara; Lingnau, Anja (Frontiers in Pediatrics, 2019)
We reviewed the literature addressing outcomes of fetal intervention of conditions that require post- natal urological management including lower urinary tract obstruction, hydrometrocolpos, congenital adrenal hyperplasia and myelomeningocele. Despite several decades of fetal intervention for these conditions, benefits remain elusive in part because of the enormous difficulty of conducting prospective randomized studies. In this review we reached the following conclusions: 1. Prenatal intervention in LUTO improves survival in the worst cases by improving pulmonary function and it may be advantageous for renal function, particularly in patients with adverse urine parameters. 2. Prenatal treatment of female fetuses at risk of having CAH reduces virilization. Non- invasive fetal DNA analysis allows earlier diagnosis, reducing the risk of treating with dexamethasone males and non-affected fetuses. 3. Fetal treatment of MMC is gaining momentum. Prospective studies including standardized urologic evaluation will determine if the encouraging results reported by some hold on the long term follow-up.